Implementasi Manajemen Risiko dalam Pengelolaan Gangguan Jaringan Telekomunikasi di Kantor Telkom Kota Padang - Nadya Rahma Oktariandani; Rahmadhona Fitri Helmi (Policy, Law and Political Research Center, 2025)
This study aims to analyze the implementation of risk management in managing telecommunications network disruptions at the PT Telkom office in Padang. The background of this study is based on the high complexity of network infrastructure and the increasing potential for disruptions due to technical, environmental, and external factors such as natural disasters and construction activities. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation studies. The results of the study show that Telkom Padang has implemented the five main stages of risk management in accordance namely risk identification, policy implementation, policy execution, risk monitoring, and contingency plan testing. The mitigation strategies implemented include mapping high-risk areas, coordinating with external parties, gradually updating infrastructure, enhancing real-time monitoring systems, providing backup materials, and conducting crisis management simulations. This implementation has proven to enhance network reliability and customer satisfaction, as well as strengthen Telkom Padang's operational resilience in addressing risk dynamics in the digital era. This research contributes theoretically to the development of risk management science in the telecommunications sector and provides practical benefits for PT Telkom Indonesia in strengthening its sustainable network risk management system.